Seaweed (Kappaphycus cottonii) farming in Brgy. Bato, Sta. Cruz, Davao del Sur supply chain and cost-benefit analysis - Gonzaga, Mikko Fernandino T.; Shuck, Vlademir A.
The growing demand for carrageenan in the international market has spurred the promotion for the growth of the seaweed industry in the Philippines. Seaweed farming has also been pushed to augment the incomes of households in coastal communities. Government agencies and different organizations have showed their support in the promotion and enhancement of the industry through various interventions that aims to benefit the small holder farmers. Brgy. Bato in Sta. Cruz, Davao del Sur has been identified to have large potential in producing seaweeds with substantial number of households involved in seaweed farming. This study analyzed the prevailing supply chain in the area. The intervention channeled through BASEAS created difference in the flow of goods in the area. Although the intervention has solved major problems that seaweed farmers were facing, the problems in the chain were transferred to the association in looking for viable markets to sell their consolidated produce. Some strategies were provided out of the internal and external factors affecting the association. Seaweeds in the farmers level are marketed either as wet or dried. Dried seaweeds offer higher prices but are more prone to price fluctuations than wet seaweeds. Using cost-benefit analysis, it was found out that unless prices for dried seaweeds reach more than PhP 60 per kilogram, farmers would gain more profit in selling their produce as wet for PhP 7 per kilogram.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao
Keywords: Seaweed industry -- Philippines